2015
DOI: 10.1016/j.bpj.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Bullet-Shaped Magnetite Nanoparticles in the Magnetotactic Bacteria Desulfovibrio magneticus sp. Strain RS-1

Abstract: Magnetotactic bacteria (MTB) build magnetic nanoparticles in chain configuration to generate a permanent dipole in their cells as a tool to sense the Earth's magnetic field for navigation toward favorable habitats. The majority of known MTB align their nanoparticles along the magnetic easy axes so that the directions of the uniaxial symmetry and of the magnetocrystalline anisotropy coincide. Desulfovibrio magneticus sp. strain RS-1 forms bullet-shaped magnetite nanoparticles aligned along their (100) magnetocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…The magnetite nanocrystallites exhibit irregular bullet-shaped morphology characteristic of the strain RS-1. 27,34 As previously reported, 31 the average length of the nanocrystallites in our cultured RS-1 strain is 53.8 6 14.2 nm, which is above the threshold for non-interacting stable singledomain (SSD) magnetite. 37,38 In addition to the SSD nanocrystallites, smaller spherical particles of about 20 nm in size occur at the ends of the chains [ Figure 1(b)].…”
Section: A Morphology and Arrangement Of The Nanocrystallitessupporting
confidence: 77%
See 2 more Smart Citations
“…The magnetite nanocrystallites exhibit irregular bullet-shaped morphology characteristic of the strain RS-1. 27,34 As previously reported, 31 the average length of the nanocrystallites in our cultured RS-1 strain is 53.8 6 14.2 nm, which is above the threshold for non-interacting stable singledomain (SSD) magnetite. 37,38 In addition to the SSD nanocrystallites, smaller spherical particles of about 20 nm in size occur at the ends of the chains [ Figure 1(b)].…”
Section: A Morphology and Arrangement Of The Nanocrystallitessupporting
confidence: 77%
“…Considering the RS-1 strain, the intracellular chains, consisting of less than ten magnetite crystallites generally organized along the [100] hard axis, can in their entirety be modeled by prolate ellipsoids. 30,41 An average length-towidth aspect ratio of 1.8 6 0.4, previously determined for our cultured RS-1 strain, 31 is equivalent to an effective demagnetizing factor of N eff ¼ 0.215 6 0.085. This corresponds to a uniaxial shape anisotropy field of 1.235 6 0.460 kOe, based on Eq.…”
Section: B Analytical Description Of Anisotropy In Magnetic Chain Asmentioning
confidence: 77%
See 1 more Smart Citation
“…In most of these studies however the effects of particle shape and elongation have been largely ignored due to the computational complexity. Recent experimental measurements of particle size distributions 13 have suggested that shape anisotropy is likely to play an important role in the magnetic anisotropy of magnetite samples, particularly at small sizes, and is also a feature of crystals in magnetotactic bacteria 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In nature, magnetotactic bacteria solve this problem by building MNPs in chain configurations to create a permanent dipole moment (PDM) in their cells. This is essentially a tool to sense the Earth's magnetic field, acting as a compass for navigation toward favorable habitats regardless of variation in bacterial morphologies …”
Section: Introductionmentioning
confidence: 99%